Modeling And Control Of Switched Reluctance Motor Drives Based On Setpoint Relay - Laurinda L.N. dos Reis; A.A.R. Coelho; O.M. Almeida; R.N.C. Almeida (Eletrônica de Potência)
This paper considers a novel ap- proach to the accurate on-line modeling of a switched reluctance motor (SRM) drive. More- over, the implementation of a simple autotun- ing technique for SRM current control based on PWM controllers using modi¯ed Ziegler-Nichols tuning method is also introduced. The proposed method is an extension of the relay feedback con- trol. It uses a setpoint relay framework to extract relevant on-line information about the process dy- namics. The proposed PWM controller has been simulated and a hardware prototype was then im- plemented with digital signal processor control to evaluate the method using a 12=8, 3-phase SRM. The experimental results of the drive model vali- date the introduced current control method.